Macroinvertebrados acuáticos como bioindicadores de la calidad del agua en las desembocaduras de los ríos Itaya y Nanay – Iquitos, Loreto. 2023 - Mozombite Mamolada, Wily (2023)
The study was carried out at the mouths of the Nanay and Itaya rivers, Iquitos City, in order to determine the biological quality of its waters, by analyzing the abundance and diversity of macroinvertebrates present using the Biological Monitoring Working Party Index (BMWP). It is evident that there is a greater diversity and abundance of macroinvertebrates in the waters of the mouth of the Nanay river, in relation to the mouth of the Itaya river. Likewise, the BMWP/Col Index for the mouth of the Nanay river indicates that the biological quality of its waters is within Class I, Good Quality, which means that its waters are very Clean to Clean, while the waters of the mouth of the Itaya River are within Class II, Acceptable Quality, which means that its waters are slightly contaminated. From this, the alternate hypothesis is accepted because the quality of surface water at the mouths of the Itaya and Nanay rivers is related to the abundance and diversity of macroinvertebrates present, according to the BMWP index, therefore, the hypothesis is rejected. null hypothesis.